Oxytocin in the Male Reproductive Tract; The Therapeutic Potential of Oxytocin-Agonists and-Antagonists - Stadler, Beatrix; Whittaker, Michael R.; Exintaris, Betty; Middendorff, Ralf (Frontiers in Endocrinology, 2020)
In this review the role of oxytocin and oxytocin-like agents (acting via the oxytocin receptor and belonging to the oxytocin-family) in the male reproductive tract is considered. Previous research (dating back over 60 years) is revised and connected with recently found aspects of the role oxytocin plays in male reproductive health. The local expression of oxytocin and its receptor in the male reproductive tract of different species is summarized. Colocalization and possible crosstalk to other agents and receptors and their resulting effects are discussed. The role of the newly reported oxytocin focused signaling pathways in the male reproductive tract, other than mediating contractility, is critically examined. The structure and effect of the most promising oxytocin-agonists and -antagonists are reviewed for their potential in treating male disorders with origins in the male reproductive tract such as prostate diseases and ejaculatory disorders.